Does beta-alanine supplementation enhance adaptations to resistance training? A randomized, placebo-controlled, double-blind study - Benvenutti Bueno de Camargo, Julio; Brigatto, Felipe; Zaroni, Rafael; Germano, Moises; Souza, Darlan; Bacurau, Reury; Marchetti, Paulo; Braz, Tiago; Aoki, Marcelo; Lopes, Charles (Biology of Sport, 2023)
The aim of the present study was to assess the effects of beta-alanine supplementation on muscle strength and thickness. Nineteen resistance-trained men (age: 27.3±5.5 years; height: 178±10 cm; body mass: 83.4±9.7 kg; training experience: 5.9±3.9 years) were allocated to one of the following groups: Beta-alanine (BA) (6.4 g/day of beta-alanine) or Placebo (PLA) (6.4 g/day of maltodextrin). Subjects completed 4 resistance training sessions per week for 8 weeks. The following assessments were performed before and after intervention periods: 1 repetition maximum (1RM) and 60%1RM tests in the bench press (60%1RMBENCH) and back squat (60%1RMSQUAT) exercises; muscle thickness assessment of biceps brachialis (MTBB), triceps brachialis (MTTB), and vastus lateralis (MTVL) by ultrasonography. No significant difference between groups was observed for the absolute increase (pre-post intervention) in the 1RMBENCH (mean difference = 0.8 kg; p = 0.679), 1RMSQUAT (mean difference = 0.1 kg; p = 0.992), MTBB (mean difference = 0.7 mm; p = 0.637), MTTB (mean difference = 1.4 mm; p = 0.282), MTVL (mean difference = 1.6 mm; p = 0.311), 60%1RMBENCH (mean difference = 0.5 repetitions; p = 0.670) and 60%1RMSQUAT (mean difference = 0.7 repetitions; p = 0.690). In conclusion, the 8-week training period induced significant strength and morphological responses. However, the addition of beta-alanine supplementation did not enhance these adaptive outcomes.